A Comprehensive Methodology for Solar Photovoltaic Power Plant Sizing under Land Area Constraint and Techno-Economic Considerations: A Case Study - Satriaksa, Harits; Fauzi Soelaiman, Tubagus Ahmad (ITB Graduate School Conference, 2025)
This study presents a comprehensive methodology for sizing a solar photovoltaic power plant (SPP) under land area constraints, incorporating technical and economic parameters. A case study was conducted at the Payo Selincah Power Plant (PSPP) in Jambi Province, Indonesia, encompassing three geographically constrained sites: Batanghari, VPower, and Cogindo. The total land area of these sites is 2,838, 1,596, and 1,015 m2, respectively. A high-capacity 660 Wp photovoltaic module was selected for the study, and 3D layout modeling and shading simulations were performed using PVsyst. Panel arrangements were designed to limit shading losses below 10%, ensuring performance ratios above 60%. The simulations yielded annual energy production of 515 MWh for Batanghari, 283 MWh for VPower, and 204 MWh for Cogindo. A techno economic analysis incorporating Indonesian fiscal assumptions (discount rate: 9.7%, inflation: 2.5%, tax rate: 22%) was conducted, resulting in LCOE values ranging from USD 0.048 to USD 0.052 per kWh. These values are below the feed in tariff benchmark of USD 0.085 per kWh. The internal rate of return (IRR) ranged from 14.95 to 16.72%, thus exceeding the typical 4–11% range for solar PV projects. The payback periods of these investments were less than 12.5 years, with return on investment (ROI) ranging from 41.4 to 56.1%. Furthermore, the system is anticipated to reduce greenhouse gas emissions by 8,355.0, 4,391.0, and 2,794.258,575.48, 4,473.92, and 2,862.59 tCO₂-eq over 25 years for the designated sites. These findings substantiate the technical and financial viability of implementing SPPs in environments with limited land availability.